Fluctuaciones espacio-temporales del crecimiento en Prionotus stephanophrys (Scorpaeniformes: Triglidae) del Pacífico sudcaliforniano, México - Schmitter-Soto, Juan Jacobo; Castro-Aguirre, José Luis (Revista de Biología Tropical, 1996)
The lumptail searobin is a dominant fish in the westem continental shelf of Baja California Sur. In order lO analyze growth variations by latitude and season, the study area was divided into four subareas, which were sampled in February and July 1989, March and September 1990. Comparison among growth patteros (as described by von Bertalanffy's model) was accomplished by Hotelling's T2 test, and a similarity matrix was constructed using standardized T2 values. The differences were non-significant and the distances small among subareas in summer, whereas in winter and between seasons they were noteworthy. This phenomenon is related lO the winter concentration by depth and latitude and summer dispersion of the species, as well as the reproduction taking place in summer. On the other hand, the northemmost subarea (Vizcaíno Bay), whose population may be different, was the most distant from the others. Finally, the predominance of a single year class in the southemmost subarea is interpreted as an effect of population periphery., the center of the population having a more even distribution of year classes.